ASAS STRICT LIABILITY DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Fajar Yudi Ariyanto; Lilik Mulyadi; Sigit Setyadi (Universitas Janabadra, 2018)
The study aims to examine and analyze: the strict liability principle in the criminal justice system in Indonesia and the ideal concept of strict liability principle in the Criminal Justice System. This type of research is normative research. This study uses secondary data. Data collection was done by document study and interview. Data analysis in this research is qualitative. Based on the result of the research, it is concluded that, Arrangement of strict liability principle in Criminal Justice System in Indonesia one of them can be seen in KUHP and outside KUHP. The Criminal Code does not explicitly mention the system of criminal liability held. Several articles of the Criminal Code only mention errors of intent or negligence. Outside of the Indonesian Criminal Code, the setting of strict liability principles in the Indonesian Criminal Justice System can be seen among others in the Environmental Law and Narcotics Act and the ideal concept of strict liability principle in the Criminal Justice System is explicitly affirmed in positive law, as defined in Article 35 Paragraph 2 The new Draft Penal Code, whose formula is: For certain criminal acts, the law may determine that a person may be criminally solely because of the fulfillment of the elements of the crime without regard to any errors.